Analysis of cuticular chemical profiles of Latrodectus geometricus (Araneae: Theridiidae) females and juveniles using GC×GC/qMS - Guimarães, Ingrid de Carvalho (2022)
Communication in spiders can occur by several mechanisms, such as chemical cues and the cuticular hydrocarbons (CHCs) play an important role in intraspecific recognition. Several techniques have been used to evaluate CHCs in spiders, such as Gas Chromatography with Flame Ionization Detection, Gas Chromatography coupled with Mass Spectrometric detection and recently Fourier Transformed Infrared Photoacoustic Spectroscopy. In this study, rapid-scanning two-dimensional gas chromatography with quadrupole mass spectrometry (GC×GC/qMS) was employed to assess the CHCs of L. geometricus females and juveniles of different ages. The results demonstrate that there is variation in CHCs of different body parts of females, with abdomen presenting greater number of compounds, as well as between adults and juveniles. Branched alkanes represented the majority of compounds in all samples, followed by linear alkanes, and alkenes were only present in adult’s abdomen and cephalothorax. The compounds 10-methyloctacosaneand 14-methyloctacosane; and 10-methyltriacontane and 14-methyltriacontane showed the same retention time in the 1D and were separated in the 2D. According to the results, rapid-scanning GC×GC/qMS can be considered a reliable technique to assess CHCs since it was possible to identify the spider’s cuticular compounds, and detect and separate two cases of chromatographic coelution.